Perlindungan Hak-hak Konsumen E-Commerce dalam Perspektif Hukum Positif Indonesia dan Konvensi Internasional - Saefudin Saefudin (UIN Sunan Kalijaga Yogyakarta, 2014)
In economy, consumers are usually placed as sub sides, their rights are ignored.On the contrary, producers/capitalist are always prioritied. Moreover, it develops cybereconomy such as e-commerce, e-trading, dropship and so on, the consumers position isweaker vis a vis producers’. Therefore, state must be present in regulating and protectingconsumers. Besides, global economy activities require the intervension of global andregional institution. This writing describes the concept of consumers protection in thepsoitive law of Indonesia and international covenant, especially related to e-commerce.